The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ph14040334
|View full text |Cite
|
Sign up to set email alerts
|

Transgene Delivery to Human Induced Pluripotent Stem Cells Using Nanoparticles

Abstract: Human induced pluripotent stem cells (HiPSCs) and HiPSCs-derived cells have the potential to revolutionize regenerative and precision medicine. Genetically reprograming somatic cells to generate HiPSCs and genetic modification of HiPSCs are considered the key procedures for the study and application of HiPSCs. However, there are significant technical challenges for transgene delivery into somatic cells and HiPSCs since these cells are known to be difficult to transfect. The existing methods, such as viral tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 140 publications
(222 reference statements)
0
1
0
Order By: Relevance
“…Moreover, although both the WT-hiPSCs and L274G-hiPSCs could form teratomas having similar differentiated cell types in vivo, the teratomas derived from L274G-hiPSCs were significantly smaller than those derived from the WT-hiPSCs. It is possible that the introduction of the L274G transgene via lentivirus-based transduction may have affected the OCT4 expression and proliferation rate of the L274G-hiPSCs via introduction of spontaneous mutations [ 46 ]. However, there are several studies that have shown a significant influence of cell line, passage number and site of injection on the teratoma size [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although both the WT-hiPSCs and L274G-hiPSCs could form teratomas having similar differentiated cell types in vivo, the teratomas derived from L274G-hiPSCs were significantly smaller than those derived from the WT-hiPSCs. It is possible that the introduction of the L274G transgene via lentivirus-based transduction may have affected the OCT4 expression and proliferation rate of the L274G-hiPSCs via introduction of spontaneous mutations [ 46 ]. However, there are several studies that have shown a significant influence of cell line, passage number and site of injection on the teratoma size [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 To date, several types of NPs based on polymers, metals and ceramics have been investigated in this respect; most of these studies were thus performed using a variety of stem cells including induced pluripotent stem cells (iPSCs). [15][16][17][18] For instance, Au-NPs functionalized with citrate, chitosan or bronectin, are able to enhance the differentiation of human mesenchymal stem cells (MSCs) and adipose-derived stem cells (ADSCs), respectively, into cardiomyocytes and osteoblasts. 19,20 Ag-NPs can promote osteogenic differentiation of human urine-derived stem cells (USCs) and the proliferation of MSCs, 21 while graphene-based NPs enhance the cardiomyogenic and angiogenic differentiation capacity of MSCs for cardiac tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…This review highlighted the current strategies, future perspectives, and challenges of the NPmediated diagnosis and treatment of thrombosis obstructs, atherosclerosis, hyperlipidemia, hypertension, pulmonary arterial hypertension, and ischemic stroke. Finally, Yamoah et al reviewed recent NP-mediated transgenic gene delivery to human-induced pluripotent stem cells (hiPSCs) [14]. The authors highlighted the advantages of NP-mediated transgene delivery over other methods, including high efficiency, low cytotoxicity, biodegradability, low cost, directional and distal controllability, and efficient in vivo application.…”
mentioning
confidence: 99%